Pengaruh Model Word Square Berbasis Saintifik Terhadap Hasil Belajar Tematik Siswa Madrasah Ibtidaiyah Karangdowo - Zumrotus Sa’diyah; Habibatul Imamah (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2018)
The influence of Word Square based scientific learning model on learning outcomes of fourth grade students of MI. The purpose of this study was to determine the influence of the scientific Word Square learning model on learning outcomes. This research is an experimental research method of True Experiment Design (a real experiment) with the type of pretest-posttest control group design one type of treatment. Research subject of fourth grade students of MI Karangdowo, sumberrejo, Bojonegoro. The results of the study showed that the Word Square based scientific learning model had an effect on the learning outcomes of students in class IV MI Karangdowo, Sumberrejo, Bojonegoro.